The handbook of global outsourcing and offshoring - Oshri, Ilan.; Kotlarsky, Julia; Willcocks, Leslie (Basingstoke, Hampshire : Palgrave MacMillan, 2009)
'This book offers a broad perspective on issues relating to the sourcing of systems and business processes in a national and global context. The authors examine the clients and the vendors' involvement in sourcing relationships by placing emphasis on the capabilities that each side should develop as a result of their interactions'--Provided by publisher.
Overview Of The Global Sourcing Marketplace -- Sourcing Models: What And When To Outsource/Offshore -- Country Attractiveness For Sourcing -- Supplier Core Capabilities And Strategies For Sustainability And Growth -- Leveraging Knowledge And Expertise -- Client Perspective: Vendor Selection Strategy, Retained Management Capabilities And Legal Issue -- The ITOutsourcing Life Cycle And The Transition Phase -- Governance Of Outsourcing Projects -- Managing Globally Distributed Teams -- Emerging Issues In Sourcing Strategy.
Includes bibliographical references and index.
Keywords: Offshore outsourcing; Contracting out